ANALISA PERBANDINGAN KOEFISIEN UPAH KERJA DAN BAHAN DENGAN METODE ANALISA STANDAR NASIONAL INDONESIA PADA BETON STRUKTUR 3 LANTAI PROYEK PERKANTORAN REVISTAR GRAHA DEWATA MALANG - MONE, HESRON IGNASIUS; Rasidi, Nawir (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
The purpose of Project Management is to manage management function or oversee the implementation of development such that optimal result are obtained in accordance with the requirements (specification) for the purpose of achieving this goal, it should be noted also about the quality of the building, the cost of the use and limits of implementation in order to achieve this result is always attempted execution quality control,cost control and supervision of the execution time. The specific project management better known as coefficients, wages and materials. office Revistar Graha Dewata Malang is a large â capacity building with 3 floors portal structure. Coefficient which is primarily used as a reference coefficient of SNI 2016 that have been defined, while there are coefficients on the location of the projects coefficients is the coefficient obtained from the results of the actual calculations, based on considerations of efficiency and economic cost. It would require a comparative analysis between the coefficients Analysis of National Standards and coefficients obtained from the project.Analysis of the coefficient of Indonesia National Standard for the wages of workers with the average value of the coefficient of 0.038 OH while the coefficient of project analysis for wages premises the average value of the coefficient of 0.009 OH. It can be concluded that the comparison coefficient eligible considerations of efficiency and economical is the coefficient project. Keywords: coefficient, project management, efficiency, economical